2021
DOI: 10.1177/00469580211028173
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Perceptions of Challenges with Frequent Users of Emergency Department Care in Switzerland: A Qualitative Study

Abstract: Frequent users of emergency departments (FUED; ≥ 5 ED visits/year) commonly cumulate medical, social, and substance use problems requiring complex and sustained care coordination often unavailable in ED. This study aimed to explore ED healthcare providers’ challenges related to FUED care to gain insight into the support and resources required to address FUED complex needs. An online survey was sent to all general adult emergency services within Switzerland (N = 106). Participants were asked to indicate the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Specifically to the FUED population, the findings from this study highlight the many inconveniences and limitations of the ED, particularly in the ability to meet the specific needs of the FUED population. These findings are consistent with previous research that revealed that ED staff and settings are typically not equipped to address the complex needs of FUED (e.g., social needs) [7]. As highlighted by a previous ethnographic study conducted in the ED [23], feeling unable to address these patients' needs may provoke anxiety among health care workers, which may, in turn, lead them to distance themselves from these patients.…”
Section: Reasons Leading To Health Care Services Dissatisfaction Amon...supporting
confidence: 90%
See 3 more Smart Citations
“…Specifically to the FUED population, the findings from this study highlight the many inconveniences and limitations of the ED, particularly in the ability to meet the specific needs of the FUED population. These findings are consistent with previous research that revealed that ED staff and settings are typically not equipped to address the complex needs of FUED (e.g., social needs) [7]. As highlighted by a previous ethnographic study conducted in the ED [23], feeling unable to address these patients' needs may provoke anxiety among health care workers, which may, in turn, lead them to distance themselves from these patients.…”
Section: Reasons Leading To Health Care Services Dissatisfaction Amon...supporting
confidence: 90%
“…This intervention might be developed through a participatory action research design and might aim to improve staff awareness through FUED testimonies and live exchanges [38]. In addition, given the fact that ED settings are typically not equipped to meet FUED complex needs and acknowledging the many difficulties encountered by health care workers [7,17,39], it may be important to provide them with additional ongoing supervision and coaching to help them navigate the complex situations presented by FUED. Furthermore, besides raising awareness among health care workers, it may be equally important to implement interventions specifically designed to address the complex needs of FUED in ED and primary care settings, such as case management [9,10,17,40].…”
Section: Drawing Several Recommendations To Improve Quality Of Care A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Emergency physicians and most nurses do not have specific training or the time to determine psychosocial needs and most do not know what resources are out in the community to fill in the gaps. Social services are attached to EDs but are not sufficiently staffed and trained in empowerment, care pathways, health literacy and outreach techniques [ 25 ]. Although HM seems appropriate to reduce iterative ED use in this population, HM has never been evaluated in this context.…”
Section: Introductionmentioning
confidence: 99%